1971
DOI: 10.1111/j.1651-2227.1971.tb05689.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness of the Czechoslovak 12‐ and 15‐year‐old Population

Abstract: The nature of the organism's reaction to a physi-years of age. The ratio of urban to rural population -cal load enables us to evaluate the organism's adap-fnllowed from the type Of laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1974
1974
1988
1988

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 2 publications
0
2
1
Order By: Relevance
“…Perhaps this merely reflects the difference in ability between the two groups of swimmers studied, Cunningham and Eynon (1975) having selected their swimmers on a more general basis with a much wider range of ability. Furthermore our results are considerably larger than the values reported in other research using children not engaged in intensive athletic training (Adams et al, 1961, Cumming and Cumming 1963, Cumming and Friesen 1967, Howell and MacNab 1968, Seliger et al, 1971, Shephard 1971). …”
Section: The Percentage Body Fat Calculations Shown Incontrasting
confidence: 78%
“…Perhaps this merely reflects the difference in ability between the two groups of swimmers studied, Cunningham and Eynon (1975) having selected their swimmers on a more general basis with a much wider range of ability. Furthermore our results are considerably larger than the values reported in other research using children not engaged in intensive athletic training (Adams et al, 1961, Cumming and Cumming 1963, Cumming and Friesen 1967, Howell and MacNab 1968, Seliger et al, 1971, Shephard 1971). …”
Section: The Percentage Body Fat Calculations Shown Incontrasting
confidence: 78%
“…The values for heart rate, oxygen uptake and blood lactate concentration, compared with the results from other investigations of non-handicapped groups of corresponding ages (e.g. Astrand and Rodahl 1970, Seliger et al 1971. Eriksson 1972, showed that maximal levels were displayed by the non-handicapped people.…”
Section: Discussionmentioning
confidence: 66%
“…In this study, the most trained subjects have VO2max values per kg body weight 16% higher at 13 and 16.7% higher at 14 years of age than those of the less trained subjects. However, these values were, respectively, 48% and 53% higher than those of sedentary subjects reported in the literature (9,15,17,19). For Kobayashi et al (13), the training effect on VO2max levels would depend on the moment when it is performed.…”
Section: Discussionmentioning
confidence: 72%